Endogenous retroviral solo-LTRs in human genome - Chen, Mingyue; Huang, Xiaolong; Wang, Chunlei; Wang, Shibo; Jia, Lei; Li, Lin (Frontiers in Genetics, 2024)
Human endogenous retroviruses (HERVs) are derived from the infection and integration of exogenetic retroviruses. HERVs account for 8% of human genome, and the majority of HERVs are solitary LTRs (solo-LTRs) due to homologous recombination. Multiple findings have showed that solo-LTRs could provide an enormous reservoir of transcriptional regulatory sequences involved in diverse biological processes, especially carcinogenesis and cancer development. The link between solo-LTRs and human diseases still remains poorly understood. This review focuses on the regulatory modules of solo-LTRs, which contribute greatly to the diversification and evolution of human genes. More importantly, although inactivating mutations, insertions and deletions have been identified in solo-LTRs, the inherited regulatory elements of solo-LTRs initiate the expression of chimeric lncRNA transcripts, which have been reported to play crucial roles in human health and disease. These findings provide valuable insights into the evolutionary and functional mechanisms underlying the presence of HERVs in human genome. Taken together, in this review, we will present evidences showing the regulatory and encoding capacity of solo-LTRs as well as the significant impact on various aspects of human biology.